Pendayagunaan Zakat Untuk Pemberdayaan Pendidikan Melalui Program Genpres Pada Laz Nurul Hayat Gresik - Pramestuty, Dita Kurnia; Suryaningsih, Sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2022)
This research aims to determine the utilization of zakat for educational empowerment through the genpres program (achievement generation) at Laz Nurul Hayat Gresik and to analyze the factors supporting and inhibiting the utilization of zakat for educational  empowerment through the genpres program (achievement generation) at Laz Nurul Hayat Gresik. This research is a descriptive qualitative study using the interactive data analysis techniques of Miles and Huberman; namely, data reduction, data presentation and conclusion drawing, and SWOT analysis methods. Check the validity of the data using source triangulation and technical triangulation. The results showed that the utilization of zakat funds for the empowerment of the Genpres program was given in the form of educational scholarships every month amounting to Rp. 250,000 where they also receiving coaching in the form of Islamic mentoring, volunteerism, and  entrepreneurship training. Rp. 250.000 where they also receive coaching in the from of islamic mentoring, volunteerism and entrepreneurship training. With the educational empowerment program through the Genpres program, it can reduce the number of children dropping out of school and increase student achievement motivation and social life, especially for orphans and poor people.